2022
DOI: 10.1111/ijfs.15745
|View full text |Cite
|
Sign up to set email alerts
|

Administration of xylo‐oligosaccharides improves depressive‐like behaviour in mice caused by chronic unpredictable mild stress by altering microbiota composition

Abstract: Summary Xylo‐oligosaccharides (XOS) is a functional oligosaccharide with prebiotic properties, and could be fermented by gut microbiota. In this study, the modulatory effects of XOS on emotions and behaviours at different dose were investigated based on the mouse model of chronic unpredictable mild stress‐induced depression. The result showed that 0.23 and 0.50 g kg−1 doses of XOS significantly increased sucrose preference index and decreased the immobility time in tail suspension and forced swimming tests. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Therefore, we first studied whether the CSPHs‐Ca modified with XOS could also have a prebiotic effect to help the body improve the structure of intestinal microbiota. As XOS is a good Bifidobacterium factor (Shu et al., 2022), compared to other treatment groups, probiotics (B. adolescentis and L. acidophilus) had the highest OD 600 when fermented with XOS as the carbon source, in particular, B. adolescentis reached high cell density (OD 600 > 1.4) during 24‐h culture, indicating that XOS could be well utilized by B. adolescentis and L. acidophilus (Zhang et al., 2019) (Figure 1a,b). Similarly, in the XOS‐CSPHs‐Ca‐TG treatment group, the maximum growth rate (slope of the curve) of B. adolescentis and L. acidophilus was close to that of XOS, and it enabled B. adolescentis and L. acidophilus to enter the logarithmic growth phase 2–4 h earlier than in the control and CSPHs‐Ca groups, and an OD 600 exceeding 1.0 was obtained at the end of the growth curve (Figure 1a,b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we first studied whether the CSPHs‐Ca modified with XOS could also have a prebiotic effect to help the body improve the structure of intestinal microbiota. As XOS is a good Bifidobacterium factor (Shu et al., 2022), compared to other treatment groups, probiotics (B. adolescentis and L. acidophilus) had the highest OD 600 when fermented with XOS as the carbon source, in particular, B. adolescentis reached high cell density (OD 600 > 1.4) during 24‐h culture, indicating that XOS could be well utilized by B. adolescentis and L. acidophilus (Zhang et al., 2019) (Figure 1a,b). Similarly, in the XOS‐CSPHs‐Ca‐TG treatment group, the maximum growth rate (slope of the curve) of B. adolescentis and L. acidophilus was close to that of XOS, and it enabled B. adolescentis and L. acidophilus to enter the logarithmic growth phase 2–4 h earlier than in the control and CSPHs‐Ca groups, and an OD 600 exceeding 1.0 was obtained at the end of the growth curve (Figure 1a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Consistently, Li (2021) also found that after 24 h of cultivation with Tremella fuciformis polysaccharides, Bifidobacterium and Lactobacillus could enter a logarithmic growth phase at 6 h, and the OD 600 at the endpoint of the curve could reach 1.0. However, its cell density is lower than that of XOS and XOS‐CSPHs‐Ca‐TG, which may be attributed to bifidogenic function of XOS is 10–20 times that of other polysaccharides (Shu et al., 2022). These results indicated that glycosylated peptide–calcium chelate could promote the growth of beneficial microorganisms in the intestinal tract and give full play to the benefit of prebiotics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation